2004
DOI: 10.1116/1.1824047
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bacterial cells and antibodies using surface micromachined thin silicon cantilever resonators

Abstract: This article describes a surface micromachined cantilever beam-based resonator for biological sensing applications. The study used a novel microfabrication technique of merged epitaxial lateral overgrowth (MELO) and chemical mechanical polishing (CMP) to fabricate thin, low stress, single-crystal silicon cantilever beams. The vibration spectra of the cantilever beams, excited by thermal and ambient noise, was measured in air using a Dimension 3100 Series scanning probe microscope (SPM), and in certain cases, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
75
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(76 citation statements)
references
References 20 publications
1
75
0
Order By: Relevance
“…DOI: 10.1103/PhysRevLett.102.228103 PACS numbers: 87.85.Qr, 81.07.Àb, 85.85.+j Micro-and nanomechanical cantilevers are widely used as sensitive probes for physical measurements in materials science, engineering and biology. In vacuum and air, detecting shifts in the resonance frequency enables exquisitely sensitive measurements of mass and detection of single DNA molecules, single viral particles, and single bacterial cells [1][2][3][4]. However, numerous applications in nanotechnology and the life sciences require samples to be contained in liquid.…”
mentioning
confidence: 99%
“…DOI: 10.1103/PhysRevLett.102.228103 PACS numbers: 87.85.Qr, 81.07.Àb, 85.85.+j Micro-and nanomechanical cantilevers are widely used as sensitive probes for physical measurements in materials science, engineering and biology. In vacuum and air, detecting shifts in the resonance frequency enables exquisitely sensitive measurements of mass and detection of single DNA molecules, single viral particles, and single bacterial cells [1][2][3][4]. However, numerous applications in nanotechnology and the life sciences require samples to be contained in liquid.…”
mentioning
confidence: 99%
“…However, it should be noted that any CMOS compatible material, such as Si 3 N 4 [14], can also be used to fabricate the initial slot regions, which later on needs to be selectively removed to open up the empty slot region. Previously, sensing arm of several micron long incorporating cantilever suspension from one end has been fabricated with negligible deformation [15]. However, since for the proposed structure only a short length of slot waveguide is suspended from both the ends it is expected to be mechanically sturdier.…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21][22][23][24] In the field of microbiology, studies have successfully demonstrated their use as mass sensors for pathogen detection via antibody-antigen chemistry. [25][26][27] Techniques moving away from antibody-antigen immobilisation have also been reported with the detection of yeast cells (Saccharomyces cerevisiae (S. cerevisiae)) using poly-L-lysine, 28 and the detection of Escherichia coli (E. coli) using cantilevers functionalised with mannosides. 29 These techniques also suffer from live/dead cell discrimination issues.…”
Section: Introductionmentioning
confidence: 99%